Optimalisasi Pemanfaatan Lahan Tidak Produktif Dan Optimalisasi Tanah Gambut Sebagai Bahan Tanam - Taryono Taryono; Muhammad Rifa’i; Roza Auliya Rosana MZ; Awibbi Permana Meidil Putra; Ajeng Retno Setiawati; Rifka Safira; Nolianush Hogejau; Yessy Maharani; Yuni Rahmawati Simangunsong; Sri Rahayu; Nandita Oktaviana (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
Farming on peatland is a complex task due to the low soil fertility and acidic soil pH. Careful and sustainable management is crucial for peatland agriculture. To address soil acidity in peatland, natural phosphate fertilizers or lime compounds like agricultural lime or dolomite can be used. These help neutralize H+ and Al3+ ions in the soil. Eggshells have the potential as an alternative to lime (dolomite) to raise pH. Eggshells also contain about 0.3% phosphorus and microelements (magnesium, sodium, potassium, zinc, manganese, and copper) at 0.3%. The activity took place at the Teluk Latak Village Office Hall, Bengkalis Subdistrict, Bengkalis Regency, on Wednesday, August 16, 2023. The materials used in making eggshell lime fertilizer are eggshells and soil. The tools used in this practice include a blender, a spoon, and polybags. The women of the Teluk Latak Village PKK (Family Welfare Movement) responded positively to the socialization of the use of unproductive land and peat soil as a planting medium. They showed enthusiasm and actively participated in sustainable agriculture training. In conclusion, eggshells are an alternative choice as a readily available natural phosphate fertilizer from household waste. Sustainable management is essential for the success of peatland cultivation, along with the establishment of an eggshell waste bank to convert eggshells into natural phosphorus fertilizer that can help neutralize H+ and Al3+ ions in the soil.